Juridical Analysis on the Determination of Child Custody to the Father in Divorce Cases - Lita Angraini; Teuku Saiful; Yusri Yusri (International Journal of Law, Crime and Justice, 2026)
This study examines the juridical issue of granting custody of children who have not yet reached the age of mumayyiz to the father in divorce cases, a condition that deviates from Article 105 letter (a) of the Compilation of Islamic Law, which generally places custody of children under mumayyiz age with the mother. The study aims to analyze Indonesian legal provisions concerning child custody granted to fathers, judicial considerations in court decisions on such custody arrangements, and the juridical implications for the protection of children’s rights after divorce. This research applies a juridical-normative method through literature study of books, journals, court decisions, and relevant laws and regulations. The findings show variations in judicial reasoning. The first decision emphasized mediation agreements but failed to adequately consider the father’s history of domestic violence against the child. The second decision maintained custody with the father based on the child’s factual living conditions and psychological comfort, despite the existence of threats of physical violence. The third decision restored custody to the biological mother after the threat to the child was considered to have ended. The study concludes that custody of children under 12 years old may only be transferred to the father when the mother loses custody rights due to serious negligence. Nevertheless, the child’s safety, best interests, and legal protection must remain the primary considerations, requiring stricter judicial standards and integration between family and criminal law.